IMPLEMENTASI QIYAS PERSPEKTIF PEMIKIRAN IBNU HAZM ( STUDI KASUS KEKERASAN TERHADAP ORANG TUA ): QIYAS IMPLEMENTATION OF IBNU HAZM'S PERSPECTIVE THINKING (CASE STUDY OF VIOLENCE AGAINST PARENTS) - Maulidi, Nur Fadiilah (Mitsaqan Ghalizan, 2023)
This study aims to see and study the extent to which acts of violence are committed by children against their parents, as well as how attitudes should be taken to avoid acts of violence as Muslims in the qiyad theory from the perspective of Ibn Hazm's thought. With a literature review approach, and using the collection of theories from journals, e-books, and the internet. Until this study resulted in the conclusion that there are many cases of violence perpetrated by children against parents in Indonesia, there are general factors that are the cause, including the economic crisis, pressure from the environment, stress, even to the point of being caused by it from the start. their parents did not give proper treatment to their children since childhood. Therefore, this article can help open everyone's minds, especially parents, that the need to implement early education from parents to their children is very much needed. Parents must educate, teach, and instill Islamic moral values, so that children can avoid bad behavior that will cause problems in the future. And conversely he will have noble character, always bring positive auras both within the family itself and even living in society in the future